CD5 blockade, a novel immune checkpoint inhibitor, enhances T cell anti-tumour immunity and delays tumour growth in mice harbouring poorly immunogenic 4T1 breast tumour homografts - Alotaibi, Faizah M.; Min, Wei-Ping; Koropatnick, James (Frontiers in Immunology, 2024)
CD5 is a member of the scavenger receptor cysteine-rich superfamily that is expressed on T cells and a subset of B cells (B1a) cell and can regulate the T cell receptor signaling pathway. Blocking CD5 function may have therapeutic potential in treatment of cancer by enhancing cytotoxic T lymphocyte recognition and ablation of tumour cells. The effect of administering an anti-CD5 antibody to block or reduce CD5 function as an immune checkpoint blockade to enhance T cell anti-tumour activation and function in vivo has not been explored. Here we challenged mice with poorly immunogenic 4T1 breast tumour cells and tested whether treatment with anti-CD5 monoclonal antibodies (MAb) in vivo could enhance non-malignant T cell anti-tumour immunity and reduce tumour growth. Treatment with anti-CD5 MAb resulted in an increased fraction of CD8 + T cells compared to CD4 + T cell in draining lymph nodes and the tumour microenvironment. In addition, it increased activation and effector function of T cells isolated from spleens, draining lymph nodes, and 4T1 tumours. Furthermore, tumour growth was delayed in mice treated with anti-CD5 MAb. These data suggest that use of anti-CD5 MAb as an immune checkpoint blockade can both enhance activation of T cells in response to poorly immunogenic antigens and reduce tumour growth in vivo. Exploration of anti-CD5 therapies in treatment of cancer, alone and in combination with other immune therapeutic drugs, is warranted.